SWOT Strategy Analysis to Develop SMEs in Tarakan City (A Study of Kelingan SMEs in Tarakan City) - Usman, Ferawati; Pramana, Firanda Andi (ProBisnis : Jurnal Manajemen, 2024)
This study aims to understand and analyze how marketing strategies are used for Kelingan SMEs in Tarakan City. The data used in this study is primary data, collected through direct interviews with informants. The method for selecting informants uses purposive sampling technique. The data collection methods in this study are interviews and questionnaires. The data analysis method uses quantitative descriptive analysis, specifically through SWOT analysis. The participants in this study are Kelingan SMEs in Tarakan City. The findings of this study show that almost all SMEs have positive IFAS scores, indicating a strong internal position. Furthermore, the positive EFAS scores of the SMEs indicate that they effectively utilize the opportunities in their market industry while successfully avoiding potential threats. The SWOT matrix shows that the SMEs are positioned in the SO quadrant (aggressive), meaning they utilize their strengths to seize existing opportunities.